Medical Imaging 2023: Digital and Computational Pathology 2023
DOI: 10.1117/12.2653715
|View full text |Cite
|
Sign up to set email alerts
|

Conditional generative adversarial network (cGAN) for synthesis of digital histologic images from hyperspectral images

Abstract: Hyperspectral imaging (HSI) has been demonstrated in various digital pathology applications. However, the intrinsic high dimensionality of hyperspectral images makes it difficult for pathologists to visualize the information. The aim of this study is to develop a method to transform hyperspectral images of hemoxylin & eosin (H&E)-stained slides to naturalcolor RGB histologic images for easy visualization. Hyperspectral images were obtained at 40× magnification with an automated microscopic imaging system and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…The segment anything model (SAM) [2], which has been trained on more than 1 billion masks and has significant skills for creating accurate object masks based on prompts (e.g., bounding boxes, points, sentences), is the original and best-known segmentation foundation model. Several works have revealed that SAM can fail on common medical image segmentation tasks [3], [4], [5], [6]. This is reasonable and predictable given that SAM's training set consists primarily of natural image datasets with substantial edge information.…”
Section: Introductionmentioning
confidence: 99%
“…The segment anything model (SAM) [2], which has been trained on more than 1 billion masks and has significant skills for creating accurate object masks based on prompts (e.g., bounding boxes, points, sentences), is the original and best-known segmentation foundation model. Several works have revealed that SAM can fail on common medical image segmentation tasks [3], [4], [5], [6]. This is reasonable and predictable given that SAM's training set consists primarily of natural image datasets with substantial edge information.…”
Section: Introductionmentioning
confidence: 99%
“…HSI produces images to form a three-dimensional “data cube” consisting of stacked two-dimensional (2D) images of the same scene at multiple contiguous wave bands. More recently, the technologies have increasingly been applied to enable histologic evaluation of tumors in biopsy or post-lumpectomy tissues 7 , 24 27 to enable intraoperative assessment of tissues. A variety of applications of the HSI for tumor margin imaging have successfully been demonstrated for image-guided clinical treatments involving diabetic wounds, 28 , 29 oral cancer, 30 head and neck cancer, 25 , 27 , 31 and breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the technologies have increasingly been applied to enable histologic evaluation of tumors in biopsy or post-lumpectomy tissues 7 , 24 27 to enable intraoperative assessment of tissues. A variety of applications of the HSI for tumor margin imaging have successfully been demonstrated for image-guided clinical treatments involving diabetic wounds, 28 , 29 oral cancer, 30 head and neck cancer, 25 , 27 , 31 and breast cancer. 32 34 Extensive discussions on the progress in medical applications of various hyperspectral imaging techniques are available in reviews elsewhere.…”
Section: Introductionmentioning
confidence: 99%